Brain with coexistent acoustic schwannoma and ependymoma - Haofuzi Zhang; Peng Zou; Wei Lin; Xiaofan Jiang (BMC Geriatrics)
Abstract Background This particular case is a world-first with no previous literature reports on patients presenting with both benign acoustic schwannoma and malignant ependymoma. Case presentation: A 60-year-old woman with unexplained right-sided hearing loss that had worsened progressively over 4 years, along with intermittent dizziness that had begun 3 years prior. Our preliminary diagnosis included: (1) Right acoustic neuroma; (2) Ependymoma of the fourth ventricle; and (3) Hydrocephalus. We employed the right sigmoid sinus posterior approach combined with the posterior median approach, beginning with removal of the fourth ventricle tumor and then proceeding to acoustic schwannomas resection through rotating operation positions. Conclusions: The case presented significant challenges owing to: The difficulty encountered in arriving at a diagnosis; The difficulty in choosing a suitable surgical approach; The complexity of the surgical sequence; The intricacy of the surgical process. It’s rare, complex, and had excellent surgical results.